Analisis Kemampuan Fiskal dan Pengaruhnya Terhadap Anggaran belanja Modal Kabupaten/ Kota di Sumatera Barat - Nengsih, Yeni Rafika (Jurnal Ekonomi, 2013)
The rule of logical gevernment started in the issurance of UU No. 22/1999 and UU No. 25/1999 which regulated regional autonomy and fiscal decentralization. This policy has been updated with the issuance of UU No. 32/2004 and UU No. 33/2004 have been governing the local government and financial balanced between central and local goverment. This research purpose: a) to find and overview map of fiscal capacity indiess, b) to analyze the impact of fiscal capacity for capital expenditure budget, c) to analyze the influece of block grand (DAU) for capital expenditure budget, d) to analyze the influece of specific grant (DAK) fot capital expenditure budget in the implementation of fiscal decentralization in West Sumatra during 2006-2010. Research design of exploratory used to analyze all of research problems in the 19 district/ munipicial in West Sumatra during 2006-2010 with desriptive and quantitative methode in multiple regression and pooled model f research method. The result show that fiscal capacity and spacific grant (DAK) have significant anf positive influenced to capital expenditure budget but it have negative correlated to block grant (DAU) in the implementation of fiscal decentralization in West Sumatra during 2006-2010. Overall, fiscal capacity indice of the 19 district/ munipicial in West Sumatra during 2006-2010is not different for every years (middle category). Then there is a disparity about the fund allocation that total fund allocated for basic less than a half total capital expenditure budget in Weat Sumatra.